POLICIES FOR DEAF CHILDREN IN VIETNAM - Trần, Thị Minh Phương (Nhà xuất bản Đà Nẵng, 2025)
In Vietnam, three children out of every 1,000 newborns suffer from hearing loss (in one or both ears), amounting to approximately 5,232 affected infants out of 1,744,400 live births recorded in 2023. A newborn with a hearing impairment impacts the entire family ecosystem, including parents, siblings, grandparents, work demands, family finances, stress, and the coping mechanisms of all caregivers and kin. This hearing disability presents lifelong challenges, starting with school choices and support, continuing to career preparation as adults, and extending to the ongoing cycles of marriage and family development for deaf individuals. According to the World Health Organization, hearing loss and deafness are severe disabilities that have not been adequately addressed. Many children who cannot hear are also unable to speak, which impacts their psychological well-being, social development, and peer relationships as they grow older. Deaf children face numerous disadvantages, are easily isolated, and encounter significant challenges in life. They are among the groups receiving attention from the Vietnamese government through the implementation of various service policies. To systematize these policies for deaf children in Vietnam, the author has employed a data analysis method to synthesize support measures. The results show that national policies for children with hearing loss can be categorized into early intervention and a comprehensive range of services, including medical support, educational support, social assistance, employment support, and other related policies. The study has systematized these policies to provide general support for deaf children, enabling them to access education, enhance their knowledge, and integrate into society while fostering their development in various aspects of social life. However, children with hearing impairments still face challenges in accessing policies related to inclusive education, receiving the benefits of policy programs, and obtaining legal aid information. To address these issues and enhance support for deaf children, it is crucial to implement policies that facilitate their integration into society. These should include guidance on technical processes for accessing information, along with legal awareness campaigns to meet the growing need for legal aid among deaf children.